Analysis Of The Effectiveness Of Collection Of Value-Added Tax On Trade Through Electronic Systems In Efforts To Optimize Tax Revenue In The Covid-19 Pandemi at The Directorate General of Taxes - Harjo, Dwikora; Abdullah, Sya’Adan; Arimbhi, Pebriana (Yayasan Sinergi Kawula Muda, 2023)
The Covid-19 pandemic has changed the way people carry out their daily activities; almost all activities are carried out online, leading to the increasingly rapid use of digital media, especially in the Trading through Electronic System (Perdagangan Melalui Sistem Elekronik / PMSE) sector. The Indonesian government sees great potential from the development of the digital economy. This is related to the government's efforts to provide equal treatment to conventional business actors and digital business actors. Therefore, the government enforces a policy of collecting Value Added Tax on Trading through the Electronic System. This study was conducted to determine and analyze the effectiveness of the collection of Value Added Tax on Trading through the Electronic System, along with the obstacles that arise and the efforts made to overcome them. In this study, the author uses a descriptive approach with data collection techniques in the form of literature review and field research. The results show that based on the target accuracy indicator, this policy has not run well because the actors of Trading through the Electronic System who have been appointed by the Directorate General of Taxes to deposit and report Value Added Tax on the use of taxable goods do not do so. In addition, there are providers of taxable services in PMSE from outside the Customs Area through who have not deposited the results of their collection. The problem lies in the supervision and lack of data owned by the Directorate General of Taxes. However, the Directorate General of Taxes has made a series of efforts to overcome obstacles in collecting Value Added Tax on Trading through Electronic Systems.